Availability and Distribution of Stoma Bags for Colorectal Cancer Patients: A Case Study at National Referral and Private Hospitals - Aryani, Ratna; Lalisang, Toar JM; Dahlia, Debie; Martha, Evi; Hamid, Achir Yani S; Wicaturatmashudi, Sukma; Helen, Helen (Kesmas, 2025)
Stoma bags are essential for colorectal cancer (CRC) patients with stomas. However, access and affordability in Indonesia remain challenging as the National Health Insurance (NHI) does not fully cover these devices. This study aimed to describe the availability and distribution of stoma bags for patients with CRC in national referral and private hospitals, focusing on outpatient access. A qualitative case study was conducted through observations and in-depth interviews with four enterostomal therapy nurses and six patients across three national referral hospitals and one private hospital in the Jakarta Metropolitan Area, Indonesia. Notably, the availability of stoma bags was limited in both hospital types, especially for outpatients. Most patients faced financial barriers, as they had to purchase stoma bags independently at high prices because of limited hospital supply and lack of NHI coverage. Moreover, hospital policies restricted the number of bags distributed, worsening access issues. These challenges increase stoma-related complication risk and negatively affect patients’ quality of life. Integrating stoma bags into NHI coverage, regulating prices, and improving distribution are recommended to reduce healthcare disparities and improve outcomes for CRC patients, aligning with Sustainable Development Goal 3.